EFEK JERA DAN KEPATUHAN HUKUM DALAM PENCEGAHAN KETERANGAN TIDAK BENAR PADA PERMOHONAN DOKUMEN PERJALANAN REPUBLIK INDONESIA: PERSPEKTIF DETERRENCE THEORY (Studi Kasus di Kantor Imigrasi Kelas I Khusus Non TPI Jakarta Selatan) - Pane, Bangkit Filippo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Providing false or inaccurate information in applications for Indonesian Travel Documents may undermine the integrity of immigration services and increase the risk of Indonesian citizens departing through non-procedural channels. This phenomenon is reflected in the Special Class I Non-TPI Immigration Office of Jakarta Selatan, which rejected or postponed 604 passport applications throughout 2025 due to issues including unclear travel purposes, inconsistencies in supporting documents, and discrepancies in applicants’ statements during interviews. This study aims to analyze the role of deterrence and legal compliance in preventing the provision of false information in Indonesian Travel Document applications from the perspective of Deterrence Theory. The study employs a juridical-empirical method with a qualitative approach through literature review, analysis of legislation, documentation, observation, and interviews. The findings indicate that interviews and document verification play an important role in increasing the likelihood of detecting false or inaccurate information, while the postponement and rejection of passport applications may serve as administrative consequences that encourage legal compliance. This study recommends the development of Standard Operating Procedures (SOPs) for passport services that integrate written warnings, administrative sanctions, and criminal sanctions in accordance with Article 126C of Law Number 6 of 2011 on Immigration, as well as strengthened preventive education through integrity pacts, public outreach, educational interviews, and continuous legal education. These measures are expected to establish both general and specific deterrence while increasing public legal awareness and compliance.